Split DNA over replicates or perform one amplification?. (December 2015) - Benschop, Corina C.G.; Yoo, Seong Yeon; Sijen, Titia
Abstract: We assessed various approaches for DNA profiling using the same total amount of DNA. The choice of profiling approach affects genotyping success and may in addition affect the likelihood ratio (LR).